Menggali kearifan kolektivisme: Pendekatan berbasis relasi dalam penelitian dan praktik psikologi di Indonesia - Himawan, Karel Karsten (Jurnal Psikologi Ulayat, 2024)
There is no one-size-fits-all psychological approach, especially in understanding the wide diversity of cultural contexts. Therefore, the development of psychology must be culturally attuned to the societal context. This commentary article aims to advocate the adoption of a relationship-based approach in the development and application of psychology in Indonesia. The article systematically presents thoughts on implementing relationship-based approaches in both psychological research and practices, with the intent to encourage readers to embrace a culturally sensitive perspective, particularly regarding collectivistic values, in understanding, researching, practicing, and advancing psychology in Indonesia. As one of the societies with the highest levels of collectivism globally, a relationship-based approach is crucial to consider in strengthening the role of psychology that aligns with the societal fabric.